2015
DOI: 10.1371/journal.pone.0144549
|View full text |Cite
|
Sign up to set email alerts
|

CD4+FOXP3+ Regulatory T Cells Exhibit Impaired Ability to Suppress Effector T Cell Proliferation in Patients with Turner Syndrome

Abstract: ObjectiveWe investigated whether the frequency, phenotype, and suppressive function of CD4+FOXP3+ regulatory T cells (Tregs) are altered in young TS patients with the 45,X karyotype compared to age-matched controls.Design and MethodsPeripheral blood mononuclear cells from young TS patients (n = 24, 17.4–35.9 years) and healthy controls (n = 16) were stained with various Treg markers to characterize their phenotypes. Based on the presence of thyroid autoimmunity, patients were categorized into TS (–) (n = 7) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The X chromosome is known to contain many immune-related genes ( 36 , 37 ), one of them being FOXP3 (forkhead box P3). FOXP3, a member of the forkhead family of transcription factors is an essential transcriptional regulator for the development and suppressive function of regulatory T cells (Tregs), a subset of CD4+ lymphocytes ( 35 , 38 ). Of note, Zinn et al have mapped a possible locus for autoimmune thyroid disease in TS to a critical region of X chromosome, Xp11.2-p22.1, which also contains FOXP3 gene ( 38 , 39 ).…”
Section: Turner Syndrome (Ts)mentioning
confidence: 99%
See 1 more Smart Citation
“…The X chromosome is known to contain many immune-related genes ( 36 , 37 ), one of them being FOXP3 (forkhead box P3). FOXP3, a member of the forkhead family of transcription factors is an essential transcriptional regulator for the development and suppressive function of regulatory T cells (Tregs), a subset of CD4+ lymphocytes ( 35 , 38 ). Of note, Zinn et al have mapped a possible locus for autoimmune thyroid disease in TS to a critical region of X chromosome, Xp11.2-p22.1, which also contains FOXP3 gene ( 38 , 39 ).…”
Section: Turner Syndrome (Ts)mentioning
confidence: 99%
“…FOXP3, a member of the forkhead family of transcription factors is an essential transcriptional regulator for the development and suppressive function of regulatory T cells (Tregs), a subset of CD4+ lymphocytes ( 35 , 38 ). Of note, Zinn et al have mapped a possible locus for autoimmune thyroid disease in TS to a critical region of X chromosome, Xp11.2-p22.1, which also contains FOXP3 gene ( 38 , 39 ). Mutations in the FOXP3 gene cause a rare disorder inherited in males, known as IPEX syndrome (Immune dysregulation, polyendocrinopathy, enteropathy, X-linked) that can be also characterized by ATD ( 38 ).…”
Section: Turner Syndrome (Ts)mentioning
confidence: 99%
“…The findings in TS patients are inconclusive. Lee et al demonstrated that although TS patients have a relatively higher number of Treg cells among CD4+ lymphocytes than healthy controls, these cells cannot efficiently suppress an autoimmune reaction (16). The latest study by Gawlik et al showed that the percentage of Treg cells in girls with TS and coexisting autoimmunity was lower than in the healthy controls and in TS girls without autoimmune diseases (17).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of Treg measures have been performed in Turners syndrome, a 45,X karyotype; however no changes in frequency were observed. 9 KS is associated with variable inactivation of the surplus X chromosome(s), 1 and differential expression of a number of X-chromosomal genes has been reported. 10 Our data support a link between the atypical copy number of FOXP3 in KS, a decrease in nTreg, and an increased risk of allergic disease.…”
mentioning
confidence: 99%
“…There are currently no reports of the frequency of nTreg in KS. Investigations of Treg measures have been performed in Turners syndrome, a 45,X karyotype; however no changes in frequency were observed . KS is associated with variable inactivation of the surplus X chromosome(s), and differential expression of a number of X‐chromosomal genes has been reported .…”
mentioning
confidence: 99%